2005
DOI: 10.1111/j.1460-9568.2005.04280.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin‐resistant Na+ channels in human neuroblastoma cells are encoded by new variants of Nav1.5/SCN5A

Abstract: Both tetrodotoxin-sensitive (TTX-S) and TTX-resistant (TTX-R) voltage-dependent Na+ channels are expressed in the human neuroblastoma cell line NB-1, but a gene encoding the TTX-R Na+ channel has not been identified. In this study, we have cloned cDNA encoding the alpha subunit of the TTX-R Na+ channel in NB-1 cells and designated it hNbR1. The longest open reading frame of hNbR1 (accession no. AB158469) encodes 2016 amino acid residues. Sequence analysis has indicated that hNbR1 is highly homologous with huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 48 publications
(73 reference statements)
3
53
0
Order By: Relevance
“…The former is a neonatal isoform (6,7,9,(28)(29)(30)(31), namely nNav1.5 (neonatal Nav1.5), while the latter is a mature isoform. Our and various other studies suggest that the Nav1.5 subtype of VGSCs encoded by the SCN5A gene could potentially serve as a marker of tumor metastasis and as a therapeutic target (8,(10)(11)(12)26,(30)(31)(32)(33)(34)(35)(36). Recent studies have found that the functions of VGSCs may vary with changes in mRNA splicing (2).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The former is a neonatal isoform (6,7,9,(28)(29)(30)(31), namely nNav1.5 (neonatal Nav1.5), while the latter is a mature isoform. Our and various other studies suggest that the Nav1.5 subtype of VGSCs encoded by the SCN5A gene could potentially serve as a marker of tumor metastasis and as a therapeutic target (8,(10)(11)(12)26,(30)(31)(32)(33)(34)(35)(36). Recent studies have found that the functions of VGSCs may vary with changes in mRNA splicing (2).…”
Section: Discussionmentioning
confidence: 74%
“…These channels not only play important roles in various physiological activities such as growth and metabolism in glial cells (19), but also in cell cycle regulation, proliferation, metastasis, invasion and apoptosis of astrocytoma cells (8,(19)(20)(21)(22)(23)(24)(25). VGSCs are mainly expressed in tumors of epithelial origin, and can participate in the biological behaviors of tumor cells, including direct spread, lateral movement, galvanotaxis, invasion and the secretory activity of the membrane (8,26,27). In the present study, we proposed that various VGSC subtypes may be related to the occurrence and development of astrocytoma, and we carried out a series of assays to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, two splice variants of Na v 1.5, hNbR1 and hNbR1 -2, differ in the presence or absence of exon 18 as a result of exon skipping. hNbR1, which includes exon 18, has a lower I Na activation, along with lower peak current and average range of I Na than hNbR1 -2, which does not include exon 18 [46]. The functional significance of the presence of these splice variants in cells has yet to be investigated, but these results suggest that hNbR1 may be more easily activated and deactivated, leading to increased excitability.…”
Section: Alternative Splicing Of Ion Channel Genesmentioning
confidence: 76%